Crop‐dominated landscapes have higher vector‐borne plant virus prevalence. Issue 4 (5th December 2016) - Claflin, Suzi B.; Jones, Laura E.; Thaler, Jennifer S.; Power, Alison G.
Summary: Landscape composition affects local arthropod biodiversity, including herbivorous insects and their predators, yet to date landscape effects on insect‐vectored plant diseases have received little attention. Here, we examine how landscape composition affects the prevalence of a viral pathogen in host plants, and the role the arthropod vector assemblage plays in mediating landscape effects. We measured the effect of landscape composition (measured as percentage of cropland and unmanaged land) on the plant virus Potato virus Y ( PVY ), its aphid vectors, and their coccinellid predators during the 2012 and 2013 field seasons at 19–21 farms. In both years, we found a positive relationship between final virus prevalence and percentage of cropland within 500, 1000 and 1500 m surrounding study sites. Percentage of cropland also had a significant negative effect on aphid species richness, and the aphid community composition in turn affected PVY prevalence. By contrast, landscape composition had no measurable effect on coccinellid abundance or species richness in this study. Synthesis and applications . Our work demonstrates that landscape composition plays an important role in vector‐borne pathogen spread, and that pathogen spread appears to be mediated by the effects of the landscape on the insect vector community. The small spatial scale (≤1500 m) of the effects seen in our study indicates that on‐farm management practices have the potential to reduce virus prevalence on small‐scale farms. Farmers may be able to reduce Potato virus Y prevalence by on‐farm diversification, by isolating potato fields from other agricultural crops, and by not using saved potato seed. Abstract : Our work demonstrates that landscape composition plays an important role in vector‐borne pathogen spread, and that pathogen spread appears to be mediated by the effects of the landscape on the insect vector community. The small spatial scale (≤1500 m) of the effects seen in our study indicates that on‐farm management practices have the potential to reduce virus prevalence on small‐scale farms. Farmers may be able to reduce Potato virus Y prevalence by on‐farm diversification, by isolating potato fields from other agricultural crops, and by not using saved potato seed.